The European legal framework and rural development policies - Prete F.; Capone R. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
The chapter offers a detailed examination of the legislation concerning EIPs. The European rural development policy integrates the rural knowledge system into the wider strategy for the consolidation of research and innovation in agriculture and forestry. Knowledge transfer and the dissemination of information in agriculture and forestry become priorities via the three key actions: strengthening of the human capital of the economic actors in rural areas, integration and networking between rural social and economic actors, and governance of the knowledge system involved in the “European Innovation Network” via networking and coordination. The EIPs follow the “interactive” innovation model, which concentrates on the creation of demand-driven partnerships, i.e. using a bottom-up approach, and bringing farmers, advisors, researchers, businesses and other actors (e.g. civil society, NGOs or government bodies) together in the so-called Operational Groups (OG). Since European legislation now appears to be more aware of the benefits deriving from investment in research and innovation, it would be desirable for the national and regional authorities to agree on a coordinated strategy to allow the many networks in the vast knowledge and innovation system to identify clear objectives and working methods.